Schwann cells genetically modified to express S100A4 increases GAP43 expression in spiral ganglion neurons in vitro. Issue 4 (4th July 2017) - Lei, Li; Tang, Li
ABSTRACT: Schwann cells (SCs) have been reported as a possible source of neurotrophic support for spiral ganglion neurons (SGNs). This study was aimed to investigate whether S100A4 was contributed in the functional effects of SCs on SGNs. SCs were transfected with S100A4 vector or small interfering RNA (siRNA) against S100A4, and the transfection efficiency was verified by quantitative PCR (qPCR) and Western blot. The migration of transfected SCs was determined by Transwell assay, and the expression levels of vascular endothelial growth factor precursor (VEGF) and matrix metallopeptidase 9 (MMP-9) were measured by Western blot. Co-culture of either S100A4 overexpressed or suppressed SCs with SGNs, and the growth associated protein 43 (GAP43) expression in SGNs was detected by immunofluorescence (IF), qPCR and Western blot. The migration of SCs was significantly enhanced by S100A4 overexpression ( P < 0.001), while was suppressed by S100A4 knockdown ( P < 0.01). Further, the expressions of VEGF and MMP-9 were notably up-regulated by S100A4 overexpression, while were down-regulated by S100A4 knockdown. Moreover, co-culture with the S100A4 overexpressed SCs significantly increased the expression of GAP43 in SGNs ( P < 0.01). As expected, co-culture with S100A4 knockdown SCs decreased GAP43 level ( P < 0.05). S100A4 enhanced the migratory ability of SCs. SCs genetically modified to overexpress the S100A4 could up-regulate the GAP43 expression in SGNs.